PLEASE HELP! I don’t understand
2 answers:
Answer:
![\frac{\sqrt{2-\sqrt{3} } }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B2-%5Csqrt%7B3%7D%20%7D%20%7D%7B2%7D)
Step-by-step explanation:
![sin(\frac{u}{2} =\sqrt[+]{\frac{1-cosu}{2} } =\sqrt{\frac{1-cos30^0}{2} } \\=\sqrt{(\frac{1-\frac{\sqrt{3} }{2)} }{2} } \\=\sqrt{\frac{2-\sqrt{3} }{4} } \\=\sqrt{\frac{2-\sqrt{3} }{\sqrt{4} } } \\=\sqrt{\frac{2-\sqrt{3} }{2} } \\](https://tex.z-dn.net/?f=sin%28%5Cfrac%7Bu%7D%7B2%7D%20%3D%5Csqrt%5B%2B%5D%7B%5Cfrac%7B1-cosu%7D%7B2%7D%20%7D%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%3D%5Csqrt%7B%5Cfrac%7B1-cos30%5E0%7D%7B2%7D%20%7D%20%5C%5C%3D%5Csqrt%7B%28%5Cfrac%7B1-%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B2%29%7D%20%7D%7B2%7D%20%20%7D%20%5C%5C%3D%5Csqrt%7B%5Cfrac%7B2-%5Csqrt%7B3%7D%20%7D%7B4%7D%20%7D%20%5C%5C%3D%5Csqrt%7B%5Cfrac%7B2-%5Csqrt%7B3%7D%20%7D%7B%5Csqrt%7B4%7D%20%7D%20%7D%20%5C%5C%3D%5Csqrt%7B%5Cfrac%7B2-%5Csqrt%7B3%7D%20%7D%7B2%7D%20%7D%20%5C%5C)
Answer:
sqrt(2-sqrt(3))/2
Step-by-step explanation:
sin(15)=sin(30/2)=sqrt(1-cos(x))/sqrt(2)=(1-sqrt(3)/2)/sqrt(2)
Again we don't like compound fractions so multiply top and bottom inside sqrt( ) by 2.
sin(15)=sqrt(2-sqrt(3))/sqrt(4)
simplify
sin(15)=sqrt(2-sqrt(3))/2
You might be interested in
Answer: A union B = B
The first one should’ve said A intersects B = A because the entirety of A exists in B
Answer: ![\sqrt{2}a-\sqrt{3}a-2\sqrt{a}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7Da-%5Csqrt%7B3%7Da-2%5Csqrt%7Ba%7D)
Step-by-step explanation:
![\lim _{x\to \:a}\left(\sqrt{2}x-\sqrt{3}x-\frac{a}{\sqrt{x}}-\sqrt{a}\right)](https://tex.z-dn.net/?f=%5Clim%20_%7Bx%5Cto%20%5C%3Aa%7D%5Cleft%28%5Csqrt%7B2%7Dx-%5Csqrt%7B3%7Dx-%5Cfrac%7Ba%7D%7B%5Csqrt%7Bx%7D%7D-%5Csqrt%7Ba%7D%5Cright%29)
![=\sqrt{2}a-\sqrt{3}a-\frac{a}{\sqrt{a}}-\sqrt{a}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B2%7Da-%5Csqrt%7B3%7Da-%5Cfrac%7Ba%7D%7B%5Csqrt%7Ba%7D%7D-%5Csqrt%7Ba%7D)
![=\sqrt{2}a-\sqrt{3}a-2\sqrt{a}](https://tex.z-dn.net/?f=%3D%5Csqrt%7B2%7Da-%5Csqrt%7B3%7Da-2%5Csqrt%7Ba%7D)
Factor 4x2−16x+16
4x2−16x+16
=4(x−2)(x−2)
Answer:
4(x−2)(x−2)
1x68
2x34
4x17
Hope that helps